Hyperuricemia contributes to glucose intolerance of hepatic inflammatory macrophages and impairs the insulin signaling pathway via IRS2-proteasome degradation - Zhao, Hairong; Lu, Jiaming; He, Furong; Wang, Mei; Yan, Yunbo; Chen, Binyang; Xie, De; Xu, Chenxi; Wang, Qiang; Liu, Weidong; Yu, Wei; Xi, Yuemei; et al. (Frontiers in Immunology, 2022)
Aim: Numerous reports have demonstrated the key importance of macrophage-elicited metabolic inflammation in insulin resistance (IR). Our previous studies confirmed that hyperuricemia or high uric acid (HUA) treatment induced an IR state in several peripheral tissues to promote the development of type 2 diabetes mellitus (T2DM). However, the effect of HUA on glucose uptake and the insulin sensitivity of macrophages and its mechanism is unclear. Methods: To assess systemic IR, we generated hyperuricemic mice by urate oxidase knockout (UOX-KO). Then, glucose/insulin tolerance, the tissue uptake of 18F-fluorodeoxyglucose, body composition, and energy balance were assessed. Glucose uptake of circulating infiltrated macrophages in the liver was evaluated by glucose transporter type 4 (GLUT-4) staining. Insulin sensitivity and the insulin signaling pathway of macrophages were demonstrated using the 2-NBDG kit, immunoblotting, and immunofluorescence assays. The immunoprecipitation assay and LC-MS analysis were used to determine insulin receptor substrate 2 (IRS2) levels and its interacting protein enrichment under HUA conditions. Results: Compared to WT mice (10 weeks old), serum uric acid levels were higher in UOX-KO mice (WT, 182.3 ± 5.091 μM versus KO, 421.9 ± 45.47 μM). Hyperuricemic mice with metabolic disorders and systemic IR showed inflammatory macrophage recruitment and increased levels of circulating proinflammatory cytokines. HUA inhibited the nuclear translocation of GLUT-4 in hepatic macrophages, restrained insulin-induced glucose uptake and glucose tolerance, and blocked insulin IRS2/PI3K/AKT signaling. Meanwhile, HUA mediated the IRS2 protein degradation pathway and activated AMPK/mTOR in macrophages. LC-MS analysis showed that ubiquitination degradation could be involved in IRS2 and its interacting proteins to contribute to IR under HUA conditions. Conclusion: The data suggest that HUA-induced glucose intolerance in hepatic macrophages contributed to insulin resistance and impaired the insulin signaling pathway via IRS2-proteasome degradation.